ZnO/WS2 Hybrid Material, for NO2 Detection, via the Combination of AACVD and APCVD Techniques - Shuja Bashir Malik; Eduard Llobet; Fatima Ezahra Annanouch (Proceedings)
We report for the first time the successful synthesis of ZnO/WS2 hybrid material using a combination of aerosol-assisted chemical vapor deposition (AA-CVD) and atmospheric pressure CVD techniques. The morphology and the composition of the grown films were investigated and the results confirm the co-existence of both materials. Moreover, gas-sensing results against 500 ppb of NO2 revealed the influence of WS2 material on the ZnO gas-sensing performance. The operating temperature shifted towards lower values, from 300 °C to 150 °C. Furthermore, at room temperature, the ZnO/WS2 sensor was able to detect NO2 at ppb level.